Hukum Mencegah Kehamilan Perspektif Imam Ghazali dan Syekh Abdullah Bin Baaz - Rifdatus Sholihah (AL-HUKAMA, 2019)
This article discusses the law of preventing pregnancy from the perspective of Imam Ghazali and Sheikh Abdullah bin Baaz. Preventing pregnancy according to Islamic law is permissible. Delaying pregnancy means preventing the pregnancy temporarily, to give a distance to the previous birth. While limiting pregnancy has the meaning of preventing pregnancy forever after having a certain number of children. Pregnancy restrictions like this, are not allowed. Shaykh Abdullah bin Baaz argues that preventing pregnancy, either by 'azl, pills, condoms, and so on is basically haram because it is contrary to maqasid shari'ah, which limits the existence of offspring, but then there are exceptions that make the law permissible, namely because the existence of a dharurat. This is different from Imam Ghazali's assertion, that the Family Planning law which is based on the ‘azl law is permissible because there is no text that shows the prohibition.